PLANT GENE PROMOTERS RESPONSIVE TO PATHOGEN INVASION - O. G. Smirnova; A. V. Kochetov (Вавиловский журнал генетики и селекции)
Gene networks controlling plant defense against pathogens are rather complex. They may involve hundreds of genes. Infection induces considerable changes at different levels: molecular-genetic, biochemical, physiological, and morphological. These changes manifest themselves locally (near the invasion site) or systemically. The reconstruction of particular gene networks responsible for defense against pathogenic bacteria, fungi, and viruses is an important step in the elucidation of the underlying molecular mechanisms as well as for the development of new approaches to crop improvement. The transcription levels of genes involved in the defense mechanisms commonly increase in response to pathogen invasion. Thus, investigation of their promoters is important for detection of new transcriptional factors controlling their activity and for search for new genes involved in pathogen response. It seems desirable to employ pathogen-responsive promoters to make plant cultivars resistant to various pathogens by gene engineering techniques. In this paper, we present data on promoters of pathogen-responsive genes with experimentally verified transcription patterns annotated in the TGP (TransGene Promoters) database. TGP may be used as a source of information for both interpretation of transcriptomic data and design of gene engineering constructs to obtain agricultural plants with improved resistance against various pathogens.